Estratégias interacionais presentes em Os sete gatinhos, de Nelson Rodrigues - Medeiros, Rosangela Garcia (2007)
Language has as principal function to transmit information among the speakers. Besides that, it's a way to provide the members of a community different acts and behavior, considering the functioning and the established rules for the social group in which they are inserted. The objective of this work is to verify the present characteristics on the interacional process between the characters of the play Os sete gatinhos and the elements that compete for the establishment of relations on linguistic interaction, so present on spoken language, pointed out on a theater text. The present study begins from a small sample of international elements in the play and showing how the characters face the problems, for example, the use of pronouns, the "ready sentences" and the relations of knowledge that each one introduces, the diminutive and the intentionality that the use of this words can suggest in the context; the choice of a slang vocabulary and a lot of relations possible among the speakers that feel the need to preserve the face in front of these situations. The emotions, feelings and opinions present on the character's conversations reflect, in the text, marks of the speech